The fracturing of Rousseau's social contract - Fryer, Melissa Zoe, author; MacDonald, Bradley J., advisor; Davis, Charles, committee member; Trembath, Paul, committee member (Colorado State University. Libraries, 2014)
Although not without debate, hydraulic fracturing, or fracking, has become the primary extraction method for hard to reach natural gas trapped in shale rock around the globe. In the United States, fracking for natural gas has alleviated the need for foreign oil by creating a domestic fuel source, facilitating job creation, and sparking contentious debates from California to New York. The most prevalent arguments from the citizens against the technique are the potential risks posed to the air, water, human, and animal health from the methane and carcinogenic byproducts released into the atmosphere, the threat of water contamination, and the risks posed to those who live, work, and play in the vicinity of well pads. Citizens have organized in shale rich states in opposition to the extraction technique to protect their families and neighbors, and for the stewardship of future generations. Yet others claim that fracking for natural gas is a safe technique to extract clean burning, domestic fuel. Looking through the lens of Jean Jacques Rousseau, this work will use hydraulic fracturing as a case study to evaluate the relevance of theoretical concepts as: the state of nature, the common good, the general will, and the Sovereign. The state of nature, according to Rousseau, was the original source for virtuous qualities in humans, before the driving passions and desires of greed, competition, and corruption arose in society. Due to the redefinition of nature that occurred during the intellectual revolution of the 16th and 17th centuries that created the dichotomy wherein humans either live in society or in nature, Rousseau interpreted the state of nature to be inclusive and attempted to deconstruct this dichotomy. I argue, with Rousseau, that once one realizes the interconnectedness of humans, nature, and society through experience and the development of a sense of place, one can access the original and virtuous dispositions that existed in the state of nature. The common good is the concept that explains that what makes the collective society flourish and attain well-being. Rousseau believes that the common good can be realized through strong virtuous morals and acceptance of the two-fold responsibility of humans: that one must develop an interest in those in the community around them, and then one must have a duty to that interest. Each individual has the potential to recognize the common good, which is expressed through the general will. This will is the common expression of the good through democracy in order to make laws that are by the people and for the people. The Sovereign's primary role is to enact this general will into law. Rousseau's concepts will be applied to the reality of hydraulic fracturing in the United States in order to access the cohesiveness of the modern social contract. First, I argue that fracking is against the common good of society through the intensive consumption of fresh water and waste produced, the risks posed to the environment and life around the wells, and the decline in the quality of life which does not ultimately promote health, well-being, and flourishing for a community. Next, in some Colorado cities, the citizens have expressed their general will to ban hydraulic fracturing through an act of popular sovereignty, as required by Rousseau's social contract. I then discuss how the general will is not being enacted by the Sovereign, as required by the contract. Instead, the people and some cities in Colorado are entrenched in litigation, based on the people's expression of the common good. Finally, I argue that the Sovereign, and some representatives of government, are enraptured by the desires and passions of the individual will, which is the third fracture in Rousseau's social contract. The fracturing of the social contact, according to Rousseau, deems for a dissolution of government. However, throughout this work, I show some potential ways in which society can learn to realize what is commonly good for all through a sense of place, through recognizing that we all have a duty and interest in others, and to attain well-being and health through a flourishing environment.
Keywords: hydraulic fracturing; common good; fracking; nature; Rousseau; social contract